Dietary Approaches to Stop Hypertension (DASH) Intervention and Nutrition Education in A Patient With Hypertension: A Case Report - Latifah Ratna Nur Azizah; Dyah Nur Subandriani (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2025)
Hypertension is a leading cause of mortality worldwide. The Dietary Approaches to Stop Hypertension (DASH) diet is a recommended nutritional intervention to help control blood pressure through sodium restriction and increased intake of potassium, fiber, fruits, and vegetables. This case report aimed to describe the implementation of a DASH diet intervention combined with nutrition education in a hypertensive patient. A 59-year-old female client with a history of hypertension and obesity (BMI 35.6 kg/m²) presented with a baseline blood pressure of 151/92 mmHg and an unbalanced dietary pattern. Nutritional assessment identified excessive energy and sodium intake, as well as inadequate fruit consumption. The intervention consisted of a hypocaloric DASH diet with a 500-kcal energy deficit and high-fiber menu modification, implemented over a short intervention period of five days, accompanied by nutrition education using leaflet media. Following the intervention, blood pressure decreased from 151/92 mmHg to 123/83 mmHg, while body weight slightly decreased from 84.4 kg to 84.1 kg. In addition, the nutrition knowledge score improved from 60 to 90. Although the intervention duration was short, these changes indicate a positive short-term response to the DASH diet and nutrition education. In conclusion, a short-term DASH diet intervention combined with nutrition education may provide preliminary benefits in improving blood pressure, dietary behavior, and nutrition knowledge in hypertensive patients. However, longer-term interventions are required to confirm sustained clinical effects.